PKM Peningkatan Pengetahuan Remaja Putri Mengenai Vulva Hygiene dalam Upaya Promotif dan Preventif di SMP Nurul Jadid - Kholisotin Kholisotin; Ayyul Fariqoini; Riskiyeh Riskiyeh; Inaya Wulandari (Universitas Nurul Jadid, 2021)
Reproductive organs are one of the organs of the body that are sensitive and require special care. Knowledge and good care are the determining factors in maintaining reproductive health. One of the symptoms of abnormalities or disease in the reproductive organs is vaginal discharge. Vaginal discharge is a very common symptom experienced by most women. All women of all ages can experience vaginal discharge. Based on research data on women's reproductive health, it shows that 75% of women in the world will suffer from vaginal discharge, at least once in their life. More than 70% of Indonesian women experience vaginal discharge caused by fungi and parasites such as pinworms or protozoa (Trichomonas vaginalis). This figure is sharply different from Europe which is only 25% because the weather in Indonesia is humid so it is easy to be infected with the Candida albicans fungus which is one of the causes of vaginal discharge. One of the efforts in the maintenance and care of genitalia is with health education. Because the more information obtained can affect or increase one's knowledge, and knowledge raises awareness which will eventually change one's behavior according to his knowledge.